2021
DOI: 10.1186/s12879-021-05819-z
|View full text |Cite
|
Sign up to set email alerts
|

Continuous hypergammaglobulinemia and proteinuria after the recovery of the visceral Leishmaniasis: a case report

Abstract: Background Kidney involvement of visceral Leishmaniasis is previously reported, but knowledge is limited. Hypergammaglobulinemia is common in visceral leishmaniasis patients. Whether hypergammaglobulinemia after leishmaniasis depletion can cause kidney injury is not well reported yet. Case presentation We reported a patient who recovered from visceral Leishmaniasis but showed persistent hypergammaglobulinemia and elevated urinary protein. Kidney bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…There are only a few studies on hypoimmunoglobulinemia in lymphoproliferative diseases. In the study of lymphoproliferative diseases with hypergammaglobulinemia, most of them are reported as individual case [2][3][4] and the number of cases is limited, mainly including hemangioimmunoblastic lymphoma and chronic lymphocytic leukemia [5] . There is no related study on lymphoma complicated with hypergamma globulinemia.…”
mentioning
confidence: 99%
“…There are only a few studies on hypoimmunoglobulinemia in lymphoproliferative diseases. In the study of lymphoproliferative diseases with hypergammaglobulinemia, most of them are reported as individual case [2][3][4] and the number of cases is limited, mainly including hemangioimmunoblastic lymphoma and chronic lymphocytic leukemia [5] . There is no related study on lymphoma complicated with hypergamma globulinemia.…”
mentioning
confidence: 99%